IoT Based mobile application using rain sensor / Siti Nur Syakirah Suliman - Suliman, Siti Nur Syakirah (2021)
Water sensor technology is required to detect the existence of water for any occasion including to provide warning and allow prevention of water in time outside or inside of the building. The most obvious disadvantage of water sensor technology in the market is that it is stand-alone product. It does not have the feature where user can monitor the product from far. Thus, this project’s purpose is to provide a new unique and innovative way to improve user’s experience in using rain sensor application specifically in monitoring and controlling the device by combining rain sensor application and mobile application. IoT Based Mobile Application Using Rain Sensor allows the roof to automatically cover the drying clothes or food outside of the house when the rain sensor detects the presence of water. Mobile application will show the status of the roof for the user to monitor. The mobile application also comes with features of rain data history for the user to see the trend of raining activity for the past few days. The user also can control the roof using the mobile application. This project aims to identify user requirements for IoT Based Mobile Application Using Rain Sensor, designing the rain sensor application that will connect to the mobile phone, designing the mobile application that will connect to the rain sensor application and development and demonstration of the IoT Based Mobile Application Using Rain Sensor. This project used the android platform. The target user of this project would be a general public user from age 45 and above who prefer use conventional way to dry clothes or food under the sun or outside of their house that live in Malaysia. IoT Methodology and Mobile Application Development Lifecycle (MADLC) and are the approaches employed to complete this task. In the future, this project is recommended to include sign up and sign in page that enable the user to see their profile on mobile application followed by weather forecast feature to allow the user to see the weather and push notification to acknowledge the user about raining activity at their house area.